Vaccination with an Attenuated Mutant of Ehrlichia chaffeensis Induces Pathogen-Specific CD4(+) T Cell Immunity and Protection from Tick-Transmitted Wild-Type Challenge in the Canine Host - McGill, Jodi L.; Nair, Arathy D.S.; Cheng, C. M.; Rusk, R. A.; Jaworski, Deborah C.; Ganta, Roman R. (My University, 2016)
Ehrlichia chaffeensis is a tick-borne rickettsial pathogen and the causative agent of human monocytic ehrlichiosis. Transmitted by the Amblyomma americanum tick, E. chaffeensis also causes disease in several other vertebrate species including white-tailed deer and dogs. We have recently described the generation of an attenuated mutant strain of E. chaffeensis, with a mutation in the Ech_0660 gene, which is able to confer protection from secondary, intravenous-administered, wild-type E. chaffeensis infection in dogs. Here, we extend our previous results, demonstrating that vaccination with the Ech_0660 mutant protects dogs from physiologic, tick-transmitted, secondary challenge with wild-type E. chaffeensis; and describing, for the first time, the cellular and humoral immune responses induced by Ech_0660 mutant vaccination and wild-type E. chaffeensis infection in the canine host. Both vaccination and infection induced a rise in E. chaffeensis-specific antibody titers and a significant Th1 response in peripheral blood as measured by E. chaffeensis antigen-dependent CD4(+) T cell proliferation and IFN. production. Further, we describe for the first time significant IL-17 production by peripheral blood leukocytes from both Ech_0660 mutant vaccinated animals and control animals infected with wild-type E. chaffeensis, suggesting a previously unrecognized role for IL-17 and Th17 cells in the immune response to rickettsial pathogens. Our results are a critical first step towards defining the role of the immune system in vaccine-induced protection from E. chaffeensis infection in an incidental host; and confirm the potential of the attenuated mutant clone, Ech_0660, to be used as a vaccine candidate for protection against tick-transmitted E. chaffeensis infection.
Citation: McGill, J. L., Nair, A. D. S., Cheng, C. M., Rusk, R. A., Jaworski, D. C., & Ganta, R. R. (2016). Vaccination with an Attenuated Mutant of Ehrlichia chaffeensis Induces Pathogen-Specific CD4(+) T Cell Immunity and Protection from Tick-Transmitted Wild-Type Challenge in the Canine Host. Plos One, 11(2), 15. doi:10.1371/journal.pone.0148229
Keywords: Human Monocytotropic Ehrlichiosis; United-States; Anaplasma-Phagocytophilum; Humoral Immunity; Animal-Model; Ifn-Gamma